Motif dan Faktor Indonesia dalam Indonesia-Korea Comprehensive Economic Partnership Agreement (IK-CEPA) - Cazelya Aryaninda Margo Putri (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2026)
The Indonesia–Korea Comprehensive Economic Partnership Agreement (IK-CEPA) is a Free Trade Agreement (FTA) between Indonesia and South Korea, signed in 2020. The agreement aims to strengthen economic relations by enhancing trade and investment flows, particularly in strategic sectors such as high technology and renewable energy. Despite being located in different regions, Southeast Asia and East Asia, both countries have pursued deeper economic cooperation. Negotiations for IK-CEPA began in 2012 but were temporarily suspended due to differing perspectives and national interests. Furthermore, Indonesia had previously been engaged in the ASEAN–Korea Free Trade Agreement (AK-FTA). Nevertheless, these conditions did not hinder the renegotiation and eventual conclusion of IKCEPA. This study seeks to answer why Indonesia approved IK-CEPA. It aims to analyze the motives and factors underlying Indonesia’s decision to expand bilateral economic cooperation with South Korea. Using a qualitative approach, this research draws on datas, including official documents, academic literature, journal articles, and news reports. The findings indicate that economic motive serves as the primary driver, while political motive, leverage motive, contextual factor, and dynamic factor function as supporting elements that reinforce Indonesia’s decision.